The Synergy of Local and Institutional Wisdom of KUA in the Development of the Sakinah Family: A Sociological Study in Solok City - Fauzi Fauzi; Sri Yunarti; Zulkifli Zulkifli; Ramza Fatria Maulana (IJoIS: Indonesian Journal of Islamic Studies, 2025)
This study aims to analyze the role of local wisdom figures and the Office of Religious Affairs (KUA) in realizing the sakinah family in Solok City, as well as identify obstacles and challenges in the synergy of the two in family development. This study is motivated by the fact that the Minangkabau people have a strong value system based on the custom of basandi syarak, syarak basandi Kitabullah, while KUA is present as a formal state institution that carries out the function of family development through marriage guidance and religious services. The research uses a descriptive qualitative approach with a phenomenological perspective. The data was obtained through in-depth interviews with ninik mamak, Bundo Kanduang, LKAAM and KAN administrators, the Head of KUA of Lubuk Sikarah and Tanjung Harapan Districts, as well as documentation of the Sakinah family development program. The results of the study show that local wisdom figures, especially ninik mamak and Bundo Kanduang, still play a significant role in family development through premarital debriefing, instilling customary and religious values, strengthening social responsibility, and mediating domestic conflicts. Meanwhile, KUA carries out strategic functions through marriage guidance, post-marriage coaching, consulting services, and synergy with BP4. This study also found that the synergy between local wisdom and KUA has not been fully optimal because it is hampered by a shift in community values towards a more individualistic direction, limited participation due to socio-economic factors, and the lack of a strong institutionalization of cooperation between KUA and customary institutions. This study confirms that the development of the sakinah family in Solok City will be more effective if it is built through a collaborative model that integrates customary, religious, and institutional forces of the state in a contextual and sustainable manner.